A New Co-Editor Joins the American Journal of Islam and Society - Shuruq Naguib (International Institute of Islamic Thought, 2020)
It is a great honor to introduce myself as the new Co-Editor of the American Journal of Islam and Society. Developing the future of this journal is a considerable intellectual trust that I can only envisage as a collective effort to be undertaken with the journal’s excellent editorial team. Under Dr. Ovamir Anjum’s editorial leadership in the last few years, the journal established a very successful trajectory, combining high academic quality and timely treatment of topics of interest to diverse communities of readers. In this introductory note, I would like to begin by expressing my commitment to the vision behind the recent name change from the American Journal of Islamic Social Sciences to the American Journal of Islam and Society. The new name captures the multidisciplinarity of the journal’s current content. This multidisciplinarity is reflected too in the editorial team’s varied areas of expertise, to which I bring my primary academic interest in Qur’anic and tafsīr studies; my work and experiences in developing Islamic Studies as a subject in its own right in Britain, which led to my involvement in founding and launching the British Association for Islamic Studies (BRAIS); and my more recent work on Islam and Muslims in Britain. Some common threads run across these different academic interests and activities, but one mode in which they have significantly intersected for me is through questions of gender, both conceptually and institutionally. It is this last aspect of my work that I am keen to draw upon as Co-Editor of the journal.